DAMPAK KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN: BUKTI UNTUK PERUSAHAAN DI INDONESIA - Rohendi, Hendi; Apriliawati, Yeti (Indonesian Accounting Research Journal, 2024)
This study examines the impact of financial performance on firm value. The research sample consisted of 51 companies in Indonesia during the period 2015-2022 with a total of 357 observations. Furthermore, the data was estimated using panel econometric techniques including pooled ordinary least square (OLS), fixed effect model and random effect model with the help of Eviews 12. The findings confirm that financial performance has a positive and significant impact on firm value. This study contributes to signal theory, namely that with a company having good financial performance, it can be a signal for investors to provide a positive response in the form of investment that has an impact on increasing the value of the company.